Events as the Products of Cultural Tourism on the Example of the Kołobrzeg Town (Research Bulletins of the Faculty of Economic Sciences, 2015)
Events currently constitute one of the main categories of the tourist product. They are included in the group of the so-called simple tourist products. Their significance on the market of tourist services is constantly increasing. Events constitute a modern form of the promotion of a brand and a product; they facilitate access to new customers, and also create a positive image of a tourist destination. It should be emphasized that for many tourists, events constitute one of the main purposes of a tourist trip. This means that they are an essential element of the tourist attraction of a given place. In this article, the potential was demonstrated of events organized in Kołobrzeg in the context of their functioning as the products of cultural tourism. A research thesis was accepted that organization of events currently constitutes one of the main factors that determine the development of cultural tourism in a given area.
Keywords: event; tourist product; cultural tourism; Kołobrzeg